Clinical Clue and Predictive Blood Count of Hemodialysis Cathether-Related Infection: Case Series - Vanessa, Nadya; Primiawan, Tatag (Universitas Brawijaya, 2023)
Most patients with chronic kidney disease (CKD) require renal replacement therapy. Majority of hemodialysis initiation is done through a dialysis catheter access. The use of catheters double lumen (CDL) for hemodialysis has several potential complications, including infection. Catheter related bloodstream infection (CRBSI) is associated with increased morbidity and mortality in CKD patients. CRBSI therapy should not be delayed, including delays due to waiting for culture results to confirm the diagnosis. Several studies have reported the use of clinical findings and routine blood count parameters to predict CRBSI. This case series reported three cases with suspected CRBSI consisting of one woman and two men with mean age of 44.67 ± 8.21 years, mean catheter days 13 ± 6.97, and mean hemodialysis duration of 10.5 ± 13.79 month. Diagnosis CRBSI was suspected from clinical clue, i.e symptoms such as fever and chills, pain at the CDL site, and physical examination i.e body temperature and local CDL site signs. Laboratory parameters in this case series reported elevations for PLR, NLR and SIRI supporting the suspicion of bloodstream infection. All patients in this case series improved after CDL removal and antibiotics therapy. Investigation of clinical findings and routine blood count parameters can be an alternative diagnosis of CRBSI that enables prompt treatment in areas with limited facilities. Keywords: chronic kidney disease, catheter related bloodstream infection, diagnosis